2011
DOI: 10.1029/2010jd015139
|View full text |Cite
|
Sign up to set email alerts
|

The community Noah land surface model with multiparameterization options (Noah-MP): 1. Model description and evaluation with local-scale measurements

Abstract: [1] This first paper of the two-part series describes the objectives of the community efforts in improving the Noah land surface model (LSM), documents, through mathematical formulations, the augmented conceptual realism in biophysical and hydrological processes, and introduces a framework for multiple options to parameterize selected processes (Noah-MP). The Noah-MP's performance is evaluated at various local sites using high temporal frequency data sets, and results show the advantages of using multiple opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
1,871
2
11

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,036 publications
(2,121 citation statements)
references
References 91 publications
22
1,871
2
11
Order By: Relevance
“…The planetary boundary layer was depicted by the Yonsei University scheme . The land surface model employed the Noah land surface model with multi-parameterization options (Niu et al, 2011). Notably, different sets of physical options may produce different simulated results (Yu et al, 2011).…”
Section: Modelmentioning
confidence: 99%
“…The planetary boundary layer was depicted by the Yonsei University scheme . The land surface model employed the Noah land surface model with multi-parameterization options (Niu et al, 2011). Notably, different sets of physical options may produce different simulated results (Yu et al, 2011).…”
Section: Modelmentioning
confidence: 99%
“…Clearly, other variables such as temperature and humidity are also important for fire weather, and our experience has been that the Noah-based schemes, including Noah-MP (Niu et al 2011), generally emerge as better with respect to MAE and bias (not shown). This motivates us to further investigate the difference among LSMs in predicting winds.…”
Section: Discussion and Summarymentioning
confidence: 88%
“…Additionally, it described that developing a multilayer snow model to capture metamorphism of snow and intrasnow heat exchange would be able to provide immediate improvements in simulations. Niu et al (2011) reported that the Noah land-surface model with multiparameterization options (Noah MP; Niu et al 2011), which can consider a three-layer snowpack, provides better estimates of observed h s , snow density (ρ s ), and SWE than the Noah LSM. Nevertheless, the performance of Noah MP to simulate snowpack has not been validated in heavy-snowfall area in Japan.…”
Section: Introductionmentioning
confidence: 99%